EDUKASI PENCEGAHAN ANEMIA PADA REMAJA DAN CARA MENANGGULANGINYA - Yona Harianti Putri; Delia Komala Sari; Rizki Oktarini; Hartadi, Ridwan; Lugastiningsih, Qori; Arisika; Khallissah Iz’zzah Aimar; Lia Ikhwan, Hikmah; Fatrisia Ananda, Liza; Salsabilah, Aliya (Universitas Bengkulu, 2025)
Community service activities entitled